2016
DOI: 10.1155/2016/8017814
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Nanocluster Precipitation and Thermal Conductivity in Si/Ge Amorphous Multilayer Films: Effects of Cu Addition

Abstract: We have used a molecular dynamics technique to simulate the relationship between nanocluster precipitation and thermal conductivity in Si/Ge amorphous multilayer films, with and without Cu addition. In the study, the Green-Kubo equation was used to calculate thermal conductivity in these materials. Five specimens were prepared: Si/Ge layers, Si/(Ge + Cu) layers, (Si + Cu)/(Ge + Cu) layers, Si/Cu/Ge/Cu layers, and Si/Cu/Ge layers. The number of precipitated nanoclusters in these specimens, which is defined as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“… 21 The nanophases that formed in the thin films are believed to be the effect of the metal-induced crystallization of the dopant metals. 30 Although control over the nanophases and their transport properties is still challenging, it can be achieved through a desirable choice of dopant and an efficient method for thin film deposition. Among the various methods reported earlier, including atomic layer deposition, 31 molecular beam epitaxy, 32 , 33 arc-melting, 34 etc., electrodeposition is one of the most versatile fabrication methods owing to its simple operation at low temperature, low cost, and high deposition rate with flexibility to design a material with tunable properties.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“… 21 The nanophases that formed in the thin films are believed to be the effect of the metal-induced crystallization of the dopant metals. 30 Although control over the nanophases and their transport properties is still challenging, it can be achieved through a desirable choice of dopant and an efficient method for thin film deposition. Among the various methods reported earlier, including atomic layer deposition, 31 molecular beam epitaxy, 32 , 33 arc-melting, 34 etc., electrodeposition is one of the most versatile fabrication methods owing to its simple operation at low temperature, low cost, and high deposition rate with flexibility to design a material with tunable properties.…”
Section: Introductionmentioning
confidence: 99%
“… 37 , 38 Until now, the effect of Cu doping in Bi 2 Te 3 /Bi 2 Se 3 has been reported by different groups through Cu intercalation, Cu electrodeposition, etc., which has shown enhancement in the thermoelectric properties. 30 , 38 40 Recently, Chen et al have found that the formation of Cu clusters is due to migration from quintuple layers with aging. 41 Burton et al showed extremely high thermoelectric performance ( S = −390 μV K –1 ) in electrochemically copper-doped bismuth tellurium selenide thin films.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations